2004
DOI: 10.1517/14712598.4.10.1595
|View full text |Cite
|
Sign up to set email alerts
|

Human cancer gene therapy with cytokine gene-modified cells

Abstract: Cytokines can impede tumour growth and activate innate and adaptive immune responses, leading to elimination of cancer cells. For many years, it was believed that systemic administration of recombinant cytokines might become a standard treatment of different cancer types. However, due to a high toxicity of therapeutic doses and a low efficacy, even in combination with chemotherapy, this strategy is generally not accepted. On the other hand, cancer gene therapy approaches utilising cells modified with cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…4,5 Cytokine gene therapy has been extensively used for the treatment of cancer in experimental animal models and clinical trials. 6,7 Among many cytokine-based anticancer therapies, interleukin-12 (IL-12) provides one of the most significant antitumor activities in many experimental animal models. 8 We have previously demonstrated that IL-12 is effective against anaplastic thyroid carcinoma in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Cytokine gene therapy has been extensively used for the treatment of cancer in experimental animal models and clinical trials. 6,7 Among many cytokine-based anticancer therapies, interleukin-12 (IL-12) provides one of the most significant antitumor activities in many experimental animal models. 8 We have previously demonstrated that IL-12 is effective against anaplastic thyroid carcinoma in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore investigated whether IL-35, ectopically expressed by DCs, could also increase Treg cell populations in the NOD diabetes model. Interestingly, by using cytofluorometric analysis, we found that the islet protection and reduced incidence of diabetes observed in the DC 35 cell-sensitized group positively correlated with an increased percentage of CD39 + CD4 + T cells, as compared with the other groups, in pancreatic lymph nodes on day 21, but not 14 after treatment initiation (Fig. 3F).…”
Section: Dcs Ectopically Expressing Il-35ig Protect From the Developmmentioning
confidence: 86%
“…In contrast, the group receiving IGRP-pulsed DC 35 cells remained normoglycemic till the 10th week, with the percentage of diabetes incidence rising not over 25% afterwards. The most relevant difference among groups could be observed from the 14th week, when approximately 65-70% of IGRP-pulsed DC Ig -and vehicle-administered mice were hyperglycemic and only 25% of mice vaccinated with IGRP-pulsed DC 35 cells showed blood glucose levels more than 250 mg/dl (Fig. 3B) (DC 35 /IGRP vs DC Ig /IGRP, p < 0.0357; Fig.…”
Section: Dcs Ectopically Expressing Il-35ig Protect From the Developmmentioning
confidence: 97%
See 1 more Smart Citation
“…27 Unfortunately, for clinical use all DC-based vaccines must be individualized for each particular patient, are time-consuming and will probably never become an easily accessible off-the-shelf product, which is Hyper-IL6-secreting tumor vaccine in mice with RCC PJ Wysocki et al not the case with the allogeneic, whole-cell tumor vaccines. [28][29][30] In the clinical setting, there is a lack of effective adjuvant therapies, which would significantly decrease the risk of tumor relapse following nephrectomy. Therefore, in our study we have evaluated the efficacy of RENCA-H6 vaccine in such a setting.…”
Section: Discussionmentioning
confidence: 99%